E. W. Cole chasing the rainbow - Lang, Lisa (Arcade Publications, 2007)
"Melbourne entrepreneur Edward Cole (1832-1918), the publisher of Cole's Funny Picture Books"--Provided by publisher.
Includes bibliographical references (p. 87-89)
Keywords: Cole, E. W -- (Edward William) -- 1832-1918; Cole, Edward W. -- 1832-1918; Geschichte 1875-1918; Booksellers and bookselling -- Victoria -- Melbourne -- Biography; Publishers and publishing -- Victoria -- Melbourne -- Biography; Verlag; Melbourne; Biografie